The synthesis and structures of arene-substituted azadipyrromethenes. (24th November 2015) - Chanawanno, Kullapa; Hasheminasab, Abed; Engle, James T.; Ziegler, Christopher J.
Graphical abstract: We present the synthesis of several azadipyrromethenes with four peripheral arene units which can be readily generated via the well-established chalcone method. The structures of several of the compounds and their BF2 adducts are presented; we also present a study into their absorption and emission properties. Abstract: We present the synthesis of several azadipyrromethenes with four peripheral arene units which can be readily generated via the well-established chalcone synthetic method. The stability and yields of these azadipyrromethenes is highly dependent on the nature of the arene substituent, with the bis-pyridine systems exhibiting the highest degree of instability. The structures of several of the compounds and their BF2 adducts are presented; intramolecular hydrogen bonding is observed in the free base ADPMs. We also present a study into the absorption and emission properties of the ADPMs and their BF2 adducts and observe that they are also highly dependent on the identity of the substituents.